2012
DOI: 10.3109/0886022x.2011.649627
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Urinary Podocytes and Kidney Diseases

Abstract: Podocyte loss is an important component of disease progression in glomerular diseases. To some extent, the loss of podocytes can predict the degree of damage and the advancement of renal disease. Detecting the loss of podocytes in the urine could be a valuable, noninvasive method for obtaining information about the activity of the disease or the disease type, allowing the early diagnosis of glomerular diseases. One of the most robust markers that has been successfully used for urinary podocyte diagnostics is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 45 publications
1
17
0
3
Order By: Relevance
“…This approach is supported by studies showing that podocyturia correlated with biopsy severity and disease progression in various forms of glomerulonephritis, including IgA nephropathy, lupus nephritis, diabetic nephropathy, etc. [12, 3134]. …”
Section: Discussionmentioning
confidence: 99%
“…This approach is supported by studies showing that podocyturia correlated with biopsy severity and disease progression in various forms of glomerulonephritis, including IgA nephropathy, lupus nephritis, diabetic nephropathy, etc. [12, 3134]. …”
Section: Discussionmentioning
confidence: 99%
“…The difficulty of demonstrating this phenomenon with this second method is due to the very rapid onset of apoptosis and the loss of cells through urinary secretion of apoptotic podocytes. 34 This is in contrast to pancreatic b cells or adipocytes that are tissue-bound and hence more easily detectable. However, we cannot rule out the possibility that podocytes dedifferentiate upon induction of caspase-8 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Initial podocyte loss leads to foot process effacement and dedifferentiation or loss of additional podocytes, along with changes in function and numbers of mesangial, parietal epithelial, glomerular endothelial, and tubule epithelial cells. 3,33,34 These downstream events lead to basement membrane thickening and interstitial inflammation and fibrosis. The POD-ATTAC mouse, although initiated by a discrete podocyte lesion, eventually elicits a more complex whole organ functional response.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also shown that damaged podocytes are able to increase the motility of normal podocytes and can cause foot process fusion and the occurrence of proteinuria by up-regulating the expression of uPAR (Patrakka and Tryggvason, 2009). As a classic diuretic, amiloride primarily acts on distal renal tubules and blocks sodiumpotassium exchange to promote the excretion of sodium and chlorine and reduce the secretion of potassium and hydrogen ions, thus achieving diuresis (Sun et al, 2012). It has been reported that amiloride might inhibit uPAR RNA and protein synthesis in cloned tumor cell strains (Haishima et al, 2012;Shkreli et al, 2012).…”
Section: Discussionmentioning
confidence: 99%